WEBINAR ANTI BULLYING UNTUK MENINGKATKAN KESADARAN MENGENAI BAHAYA DAN CARA UNTUK MENGHADAPI BULLYING - Siska Oktari; Sabrina Puti Afifah; Nazri Sakinah; Sheila Maeshade; Jessica Berliana (Jurnal Abdimas Bina Bangsa, 2023)
This study aims to determine the effectiveness of psychoeducation on dangers and how to deal with bullying through the "No Bullying 2023" Webinar. The research was conducted using a quasi-experimental method by comparing the results of pre-test and post-test on the "No Bullying 2023" Webinar participants. Participants in this study counted 225 participants who met the criterias as such: registered and filled out the pre-test on the online form, participated in webinar activities as evidenced by filling out the attendance list and post-test, willing to provide their data for research, whose age around 10 to 30, or were in adolescent and early adult categories. The pre-test and post-test results were analyzed using a paired sample t-test and the Sig. (2-tailed) is 0.000 with a t value of 8.582 which means that there is a significant increase in knowledge of the participants in the Webinar "No Bullying 2023”